A new insight into the pigmentation of the three-spined stickleback exposed to oxidative stress: day and night study - Sokołowska, Ewa; Kulczykowska, Ewa (Frontiers in Marine Science, 2024)
The diverse and changing pigmentation of the skin allows fish to adapt to environmental conditions for survival and communication with conspecifics. However, various physical and chemical environmental factors, including pollutants, affect fish colouration. Therefore, the implementation of an analysis of skin pigmentation has been considered in fish well-being and ecotoxicological studies. A physiological colour change is achieved by the motility of melanincontaining organelles: they aggregate into the perikaryon or disperse throughout the cytoplasm of melanophores in response to various stimuli. In our study, we addressed the issue of implementing the analysis of pigment dispersion in melanophores in stickleback skin to assess the response of fish to oxidative stress. We examined pigment dispersion in day and night skin samples collected from the dorsal, lateral and ventral regions. The degree of pigment dispersion we assessed by the melanophore index. The total number of melanophores counted in the defined skin area was significantly higher in the night samples than in the day samples. Only in day samples of dorsal skin we observed the significant changes in pigment dispersion after exposure to stress: melanin was predominantly in the aggregated state. In the night samples, we did not report any response to stress in any part of the skin. Examination of pigment dispersion in melanophores in stickleback skin can be useful for assessing the welfare of fish and detecting toxic agents in the environment, but under specified conditions: in sticklebacks, it is analysis of dorsal skin during the day.